KINERJA KANTOR PERWAKILAN BADAN KEPENDUDUKAN DAN KELUARGA BERENCANA NASIONAL (BKKBN) PROVINSI RIAU DALAM PROGRAM PEMBANGUNAN KELUARGA, KEPENDUDUKAN DAN KELUARGA BERENCANA (BANGGA KENCANA) - Rizal Ade Saputra; Febri Yuliani (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2021)
Organization performance is the ability of the organization to carry out any tasks assigned to the organization to achieve the goals, objectives, mission and vision of the organization. The Riau Province BKKBN office is one of the government organizations that has the duty and function to carry out population control and the implementation of family planning in the region. The existence of a demographic bonus opportunity in Riau is the reason for the BKKBN to run the Family Development, Population and Family Planning (Bangga Kencana) program as an effort to maintain and utilize a more comprehensive demographic bonus. The realization of organizational activities and programs depends on the activities of the organization itself and the people in it. The realization of the program can be seen from the performance of the BKKBN organization in running it. The purpose of this study was to see the performance of the Riau Province BKKBN office in implementing the Proud Kencana program and to see the factors inhibiting its performance. This study uses a qualitative descriptive research method and the selection of informants using purposive sampling. Data collection techniques through observation, interviews and documentation. The results showed that the performance of the representative office of the National Population and Family Planning Agency (BKKBN) of Riau Province in the Family Development, Population and Family Planning Program (Bangga Kencana) was running well and optimally. This is measured by performance indicators, namely quantity, quality, productivity, timeliness (already going well). Meanwhile, the inhibiting factors for the performance of the BKKBN office in the implementation of the Proud Kencana program are discipline and budget because they are influenced by the Covid-19 pandemic situation and the age factor of the employees. Keywords: Performance, Organization, BKKBN Province of Riau